Neonatal and Maternal Risk Factors for Indirect Hyperbilirubinemia: A Cross-Sectional Study from Bahrain - Hasan M. Isa; Noor Y. AlBuainain; Fatema Y. Bunajem; Abdulrahman S. Masood; Yusuf A. Bucheery (International Journal of Pediatrics)
Background and Objectives. Jaundice is a common cause of hospital admission in infants presenting within the first month of life. This study is aimed at determining neonatal and maternal risk factors of indirect hyperbilirubinemia, at comparing neonates with risk factors and those without, and at assessing the type of management according to hyperbilirubinemia severity. Material and Methods. In this retrospective cross-sectional study, medical records of neonates with indirect hyperbilirubinemia who were admitted to the Pediatric Department, Salmaniya Medical Complex, Bahrain, between January 2020 and December 2020 were reviewed. Neonatal demographic data, antenatal history, birth weight, feeding type, maternal and neonatal laboratory evaluations, management, and length of hospital stay were collected and compared. Results. Out of 555 records, 404 neonates were included. Among those, 209 (51%) were males and 275 (68.1%) were Bahraini. The median indirect bilirubin level at presentation was 218 (interquartile range, 174-270) μmol/L. ABO incompatibility was the commonest risk factor for neonatal indirect hyperbilirubinemia (n=152, 37.6%) followed by glucose-6-phosphate dehydrogenase (G6PD) deficiency (n=130/400, 32.5%). Age (>25 years) was the commonest maternal risk factor (n=331, 81.9%) followed by cesarean delivery (n=137, 33.9%). Neonates with ABO incompatibility had a significantly higher mean indirect bilirubin level compared to those with other risk factors (234.9±68.5 versus 225±82.2 mmol/L, respectively) (P=0.04). Phototherapy use significantly increased along with the rise of bilirubin level (P<0.0001). Intravenous immunoglobulins (IVIG) and exchange transfusion were used in 44 (10.9%) and 14 (3.5%) patients, respectively. Neonates who received IVIG had significantly higher bilirubin levels than those who did not (P=0.005). Male newborns (P=0.008), Bahrainis (P=0.001), those with reticulocytosis (P=0.001), and those who received IVIG (P=0.001) were more prone to have associated risk factors. Conclusion. ABO incompatibility, G6PD deficiency, and older maternal age were the commonest neonatal and maternal risk factors for developing neonatal indirect hyperbilirubinemia. Bahraini, male newborns, reticulocytosis, and IVIG use were associated with these factors. Early detection of such factors through screening can aid in immediate management to prevent serious complications of this common condition.